2017
DOI: 10.1016/j.synbio.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Improving acarbose production and eliminating the by-product component C with an efficient genetic manipulation system of Actinoplanes sp. SE50/110

Abstract: The α-glucosidase inhibitor acarbose is commercially produced by Actinoplanes sp. and used as a potent drug in the treatment of type-2 diabetes. In order to improve the yield of acarbose, an efficient genetic manipulation system for Actinoplanes sp. was established. The conjugation system between E. coli carrying ØC31-derived integrative plasmids and the mycelia of Actinoplanes sp. SE50/110 was optimized by adjusting the parameters of incubation time of mixed culture (mycelia and E. coli), quantity of recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In line with the results of previous feeding studies with 13 Clabeled 8 and 13, in which none of these compounds were incorporated into 1 19 , our work showed that both compounds are shunt products branched from the biosynthetic intermediate 12 ( Fig. 1b; Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with the results of previous feeding studies with 13 Clabeled 8 and 13, in which none of these compounds were incorporated into 1 19 , our work showed that both compounds are shunt products branched from the biosynthetic intermediate 12 ( Fig. 1b; Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…SE50/110, and the mutant was named QQ-3. Both P-1 and 1 disappeared in the fermentation broth of mutant QQ-3, and were restored by trans-complementation of the acb cluster cloned on fosmid pLQ666 13 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations